Evaluation of stimulated raman scattering microscopy for identifying squamous cell carcinoma in human skin - Mittal, Richa; Balu, Mihaela; Krasieva, Tatiana; Potma, Eric O.; Elkeeb, Laila; Zachary, Christopher B.; Wilder-Smith, Petra (Lasers in surgery and medicine, 2013)
Background and Significance There is a need to develop non‐invasive diagnostic tools to achieve early and accurate detection of skin cancer in a non‐surgical manner. In this study, we evaluate the capability of stimulated Raman scattering (SRS) microscopy, a potentially non‐invasive optical imaging technique, for identifying the pathological features of s squamous cell carcinoma (SCC) tissue. Study Design We studied ex vivo SCC and healthy skin tissues using SRS microscopy, and compared the SRS contrast with the contrast obtained in reflectance confocal microscopy (RCM) and standard histology. Results and Conclusion SRS images obtained at the carbon‐hydrogen stretching vibration at 2945 cm−1 exhibit contrast related protein density that clearly delineates the cell nucleus from the cell cytoplasm. The morphological features of SCC tumor seen in the SRS images show excellent correlation with the diagnostic features identified by histological examination. Additionally, SRS exhibits enhanced cellular contrast in comparison to that seen in confocal microscopy. In conclusion, SRS represents an attractive approach for generating protein density maps with contrast that closely resembles histopathological contrast of SCC in human skin. Lasers Surg. Med. 45:496–502, 2013. © 2013 Wiley Periodicals, Inc.